Closure mappings and the problem of determining maximal frequent itemsets in data mining - Minh, Bui Duc (VNU Journal of Science: Mathematics - Physics; Vol 29 No 2, 2013)
Abstract: In data mining, association rules are considered as a fundamental problem. Process of association rules can be run in two stages. The first stage is to find all the frequent itemsets, and the second stage is to generate association rules. However, with a large database, the number of itemsets will be very large and thus the problem of finding association rules is not feasible. In this paper, the author uses he notation of closure mappings and lattice theory as a mathematical approach to show the applicability of these tools to the data mining. In particular, a method of determining maximal itemsets with the purpose of minimal scanning times of database is presented in the paper. Keywords: Closure mapping, Intersection lattice, maximal frequent itemset, coatom.